FOREIGN EXPERIENCE OF LEGAL REGULATION OF THE ACTIVITY OF THE SUBJECTS OF THE ECONOMY - Орлова, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: the article reveals the development of the theoretical foundations of economic law and process. The problems of functioning of economic entities from the position of the category "entrepreneur" are revealed. The views of scientists on the problem of regulation of the activity of subjects of economic law, as entrepreneurs and traders, are analyzed. Methods of research: the analysis of foreign experience in categories of entrepreneur and merchant is determined. Classification of international acts in the field of business entities. Results: the ways of further development of categories of business entities in the domestic legislation are determined. The conclusion is made on the need to ensure the development of domestic economic law. Discussion: problems of the national legislation and implementation of the norms of foreign legislation to the norms of domestic economic legislation.